Endoscopic versus surgical treatment for infected necrotizing pancreatitis: a systematic review and meta-analysis of randomized controlled trials - Haney, Caelán Max; Kowalewski, Karl-Friedrich; Schmidt, Mona Wanda; Koschny, Ronald; Felińska, Eleni Amelia; Kalkum, Eva; Probst, Pascal; Diener, Markus K.; Müller, Beat P.; Hackert, Thilo; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2020)
To compare outcomes of endoscopic and surgical treatment for infected necrotizing pancreatitis (INP) based on results of randomized controlled trials (RCT).